Dictator games: A meta study - Christoph Engel (Max Planck Institute for Research on Collective Goods, 2010)
Over the last 25 years, more than a hundred dictator game experiments have been published. This meta study summarizes the evidence. Exploiting the fact that most experiments had to fix parameters they did not intend to test, the meta study explores a rich set of control variables for multivariate analysis. It shows that Tobit models (assuming that dictators would even want to take money) and hurdle models (assuming that the decision to give a positive amount is separate from the choice of amount, conditional on giving) outperform mere meta-regression and OLS.
Keywords: C24; C91; D03; 330; Spieltheorie; Rationales Verhalten; Test; Meta-Analyse; Tobit-Modell